Performance and reliability of commercially available thermoelectric cells for power generation. (5th June 2016) - Ding, L.C.; Akbarzadeh, A.; Date, A.
Highlights: The performance of commercially available Bi2 Te3 TECs as heat engine is studied. The conversion efficiency in the regime of low grade heat is presented. Prolonged exposure to the high operating temperature should be avoided. The damage occurs in prolonged high temperature is irreversible. Abstract: This paper presents performance and reliability study of commercially available Bi2 Te3 thermoelectric cells (TEC1-12710T125) used as a thermoelectric generator (TEG). These TECs are tested in temperature regime from ambient temperature up to 250 °C. This paper provides simple guide to estimate energy conversion efficiency of commercially available Bi2 Te3 thermoelectric cells for power generation at a variety of operating conditions in low temperature regime. When these TECs were tested at hot side temperature of around 210 °C continuously for 7 h, their performance was seen to reduce by around 37% as compared to performance at lower temperatures. These cells when again tested at lower temperatures showed reduced efficiency and power output. This shows that the damage is irreversible although the process revert to lower hot side temperature (<100 °C). Finally this paper presents performance of these TECs when subjected to thermal cycling and continuous operation at hot side temperature of about 160 °C. It was observed that the open circuit voltage starts to jump beyond 300 cycles. This might be due to weakening of the soldered joints within the cell.